2015
DOI: 10.1007/s10549-015-3398-z
|View full text |Cite
|
Sign up to set email alerts
|

AroER tri-screen™ is a novel functional assay to estimate both estrogenic and estrogen precursor activity of chemicals or biological specimens

Abstract: The purpose of the study is to define AroER tri-screen's utility for identifying endocrine-disrupting chemicals (EDCs) that target aromatase and/or estrogen receptor (ER), and to measure the total estrogenic activity in biological specimens. ER-positive, aromatase-expressing MCF-7 breast cancer cells were stably transfected with an estrogen responsive element (ERE)-driven luciferase reporter plasmid to yield a new high-throughput screening platform—the AroER tri-screen. AroER tri-screen was capable of identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In order to elucidate the impact cell cycle-driven ER can have on palbociclib response, we utilized the C4-12 cell line which is a variant of the MCF-7 cell line but lacks an endogenous ERα [ 27 ]. We generated a stably transfected ERα (C4-12/ERα) cell line which has a transcriptionally functional ER [ 28 ] but does not need estrogen for cell growth ( Supplementary Figure 1 ). CDK4/6 inhibitors did not affect the proliferation of C4-12/ERα (Figure 1 ), indicating that proliferation of these cells does not require ER even though they have biologically active.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to elucidate the impact cell cycle-driven ER can have on palbociclib response, we utilized the C4-12 cell line which is a variant of the MCF-7 cell line but lacks an endogenous ERα [ 27 ]. We generated a stably transfected ERα (C4-12/ERα) cell line which has a transcriptionally functional ER [ 28 ] but does not need estrogen for cell growth ( Supplementary Figure 1 ). CDK4/6 inhibitors did not affect the proliferation of C4-12/ERα (Figure 1 ), indicating that proliferation of these cells does not require ER even though they have biologically active.…”
Section: Resultsmentioning
confidence: 99%
“…We have established that C4-12/ERα cells do not require estrogen for cell growth ( Supplementary Figure 1 ) but ER is activated by estrogen as seen with the up-regulation of ER regulated genes such as GREB1, TFF1 and PGR, which is also observed in the estrogen dependent MCF-7 cell line ( Supplementary Table 2 ). Analysis of C4-12/ERα cells shows no change in the G2/M-phase or checkpoint regulation genes ( Supplementary Figure 3B ); thus, the transcriptionally functional ER in this cell line [ 28 ] is not involved in cell cycle progression. Moreover, even though this cell line expresses RB, which alone is not a predictive factor of palbociclib response [ 18 , 20 , 40 42 ], a transcriptionally functional ER involved in cell cycle progression is required for the inhibitor response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a luciferase reporter system, each PBDE was tested in a C4-12ERa ERE assay for estrogenic and/or anti-estrogenic properties. The C4-12ERa ERE cells were established in our laboratory from C4-12 cells, derived from MCF-7 breast cancer cells, that are deficient in endogenous ER expression; we previously confirmed that the reporter signal is highly specific for ERa (not ERb) (Kanaya et al, 2015). In the agonist mode of this assay, cells were treated only with the individual PBDE (no cotreatment).…”
Section: Effects Of Bde-47 Bde-100 and Bde-153 On Era Through Cell-mentioning
confidence: 94%
“…MCF7aro cells (Zhou et al, 1990) were maintained in MEM supplemented with 10% FBS, 2 mM L-glutamine, 1 mM sodium pyruvate, 100 U/ml penicillin-streptomycin, and 100 lg/ml of G418. C4-12 ERaERE cells (Kanaya et al, 2015) were maintained in phenol red-free high-glucose DMEM supplemented with 10% charcoal-dextran stripped FBS (Omega Scientific, Tarzana, California), 2 mM L-glutamine, 1 mM sodium pyruvate, 100 U/ml penicillin-streptomycin, and 100 lg/ml of hygromycin. T47D cells were maintained in RPMI-1640 supplemented with 10% FBS, 2 mM L-glutamine, 1 mM sodium pyruvate, and 100 U/ml penicillin-streptomycin.…”
Section: Methodsmentioning
confidence: 99%